Moving to markets in environmental regulation lessons from twenty years of experience - Freeman, Jody.; Kolstad, Charles D.; Oxford eBooks (Oxford : Oxford University Press, 2007)
Contains essays that bring together some of the best academic minds from economics and law to take a retrospective look at the performance of market-based instruments for environmental protection. This book is intended for academics in environmental economics and law, along with policymakers and advocates.
Papers given at a one-day workshop in Santa Barbara, Calif. in 2003.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Environmental policy -- Economic aspects; Environmental protection -- Economic aspects; Emissions trading; Environmental impact charges; Wetland mitigation banking; Environmental law; Electronic books